Audit Partner Gender, Gender Diversity in the Board and Auditor Report Lag - Kalanjati, Devi Sulistyo; Putra, Ramadhan Ghea Ananda; Anam, Mohamad Khoirul (Jurnal Akuntansi dan Bisnis, 2024)
ABSTRACT This research investigates the impact of audit partner gender on audit report lag and explores whether the gender diversity of the board of directors can moderate this relationship. The study was motivated by the low representation of female audit partners in Indonesia and the need for a more efficient audit process. The research used a quantitative approach and focused on non-financial companies listed on the Indonesia Stock Exchange (IDX) from 2017 to 2021. The sample size was 2,430 observations (company-years) and was determined using the purposive sampling. The results indicated a positive association between female audit partners and audit report lag, suggesting that female audit partners may conduct more detailed audit work, leading to longer processing times than male audit partners. Additionally, the gender diversity of the board of directors was found to weaken the influence of the gender of audit partners on audit report lag. Collaboration between female audit partners and a board of directors comprising females may promote a more efficient audit process. The study suggests that regulators and professional organisations could consider implementing quotas to encourage greater female participation in the audit process.